Upaya Diplomasi Pemerintah Indonesia dalam Meningkatkan Ekspor Kopi ke Selandia Baru Tahun 2020-2022 - Trisna, Ni Putu Wulan; Priadarsini, Ni Wayan Rainy; Suwecawangsa, Adi Putra (Program Studi Hubungan Internasional FISIP Universitas Udayana, 2024)
Coffee trade barriers with major market countries encourage the Indonesian government to start organizing relationships with potential country, New Zealand. Indonesian government initiated several trade mission to strengthen countries economy connectivity, including coffee trade. Each year New Zealand imports coffee from Indonesia. However, the volume of Indonesian coffee exports to New Zealand has fluctuated greatly. Indonesia's coffee exports to New Zealand by quantity experienced 31% decline in 2019 than the previous year. That was the biggest decline over the past decade. The Indonesian government keep mobilizing diplomatic activities to promote their coffee commodity in New Zealand. Since 2020, Indonesian government considered coffee diplomacy activities that view coffee as commodity and culture at once. The regressive moment of Indonesia's coffee exports to New Zealand was finally resolved in 2021 and was still increasing in 2022. This study aims to examine the Indonesian government's diplomatic efforts in increasing coffee exports to New Zealand in 2020-2022. Researcher analyzed it qualitatively using the concept of coffee diplomacy which has dimensions of cultural diplomacy and economic diplomacy. This study found that Indonesian government's coffee diplomacy was carried out by conducting coffee as Indonesian culture and export commodity. The Indonesian government's coffee diplomacy during 2020-2022 was implemented by spreading the culture of drinking Indonesian coffee as an attraction that leads to opportunities to increase exports to New Zealand.